BEBERAPA PANDANGAN TENTANG GURU SEBAGAI PENDIDIK - Bahaking Rama (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2007)
The Education very determines of development step of a nation. The Nation prioritizing of education sector development will become the nation progress and has high civilization. In the educa- tional process consists of some factors determining. One of the factors is teacher. The teacher has right and obligation in order to run his duty as a teacher or educator. Relating with his obligation is as a teacher. The teacher is demanded to take responsibility for developing potential, grind down intelligence, and transfer knowledge and technology to the learners in order to sharpen the life of nation. While relating with his duty is as educator, the teacher is demanded to take responsibility for, besides to sharpen the learners mind, he also takes responsibility for pounding the learners’ personality and morality or character.